El problema semántico de los emoticones. Una perspectiva legal (Bridging Cultures, 2019)
The general theory of law has historically analyzed the relationship between language andlaw and tried to provide solutions to the problems that this causes when interpreting the law.The new media presents challenges for these schemes; we now face problems posed not bywords (which may be vague or ambiguous) but rather by virtual symbols. The question, then,is how to interpret them; can the emojis have legal transcendence or they are simple symbols?This paper is to emphasize that the law faces a new problem of interpretation.
Keywords: General theory of the Law; Interpretation of the Law; Language problems; Emojis